Rapid screening of natural products for antimycobacterial activity by using luciferase-expressing strains of Mycobacterium bovis BCG and Mycobacterium intracellulare. - Shawar, R M (1997)
The object of this study was to investigate the ability of a rapid luciferase assay to detect antimycobacterial activity in plant extracts. Recombinant strains of Mycobacterium bovis BCG (rBCG) and Mycobacterium intracellulare expressing firefly luciferase were used as the test organisms. Assays were conducted in a 96-well minitube format under biosafety level 2 conditions. Control and test wells were sampled immediately after inoculation and after 3 (recombinant M. intracellulare) and 5 (rBCG) days of incubation to measure luminescence with a microplate luminometer, and the relative change in luminescence was calculated as a percentage of control values. As an alternative test method, Alamar blue was added after 12 days of incubation, and changes in color were read visually. A total of 480 extracts were tested. Sixteen extracts were active against rBCG, and of those, seven were also active against recombinant M. intracellulare. With activity defined as a relative change in luminescence of < or = 1% (i.e., > or = 99% inhibition) and a persistence of blue color after addition of Alamar blue, there was 99.0% agreement between the two methods. Our results suggest that the luciferase assay is rapid and accurate and has the potential to greatly accelerate the evaluation of antimycobacterial activity in plant extracts in vitro. With this method, it is possible to screen a large number of samples in a short period of time.